Exploration on Biological Resources to Reduce Carbon Emissions and Increase Nutritional Value of Corn (Zea mays) using Arbuscular Mycorrhizal Fungi and Glomalin - PRATAMA, YOGI; FUADI, MISRIL (Central Research Institute For Agriculture, 2024)
Zero emissions have been a prominent topic in recent years, referring to the concept of reducing or eliminating greenhouse gas emissions, particularly carbon dioxide, from human activities such as transportation, energy production, and industrial processes. Agricultural practices, such as excessive or improper application of lime, inorganic fertilizers, and pesticides, can alter the physical and chemical properties of soil, affecting the abundance and diversity of beneficial organisms that support plant growth. have demonstrated that the use of Arbuscular Mycorrhizal Fungi (AMF) and glomalin can enhance protein and amino acid content in plants. The research found that the combined treatment of AMF and glomalin yielded better results than using each treatment separately. Additionally, this study indicated that AMF and glomalin applications could improve micro-nutrient content, including Fe, Zn, and Cu. The research was conducted in the Soil Microbiology and Ecology Laboratory and the Food Production and Analysis Laboratory at the Faculty of Agriculture, Universitas Muhammadiyah Sumatera Utara, from February 2023 to June 2023. The experimental design used was a Randomized Block Design (RBD) with three treatments: control, AMF, and AMF+Glomalin. The conclusion of this research is that the use of AMF and glomalin effectively enhances the nutritional value of corn, particularly in terms of organic matter, carbohydrates, and proteins. The findings are closely aligned with Indonesia’s Vision 2045, which aims to increase agricultural productivity, maintain environmental sustainability in farming, secure food supplies, reduce greenhouse gas emissions, encourage sector collaboration, enhance agricultural education, and achieve Sustainable Development Goals (SDGs). The study demonstrates that the use of AMF+Glomalin in agriculture significantly improves soil organic matter, corn nutrition, and sustainable practices, thus contributing to Indonesia’s Vision 2045 for a better future.